Will Love Tear Us Apart: Adapting the Lyrical to the Ludic. Issue 2 (August 2016) - Calleja, Gordon
Abstract : This paper gives an insight into the design process of a game adaptation of Joy Division's Love Will Tear Us Apart (1980). It outlines the challenges faced in attempting to reconcile the diverging qualities of lyrical poetry and digital games. In so doing, the paper examines the design decisions made in every segment of the game with a particular focus on the tension between the core concerns of the lyrical work being adapted and established tenets of game design.